Economic Importance of Genetic Improvements in Milk Production, Reproduction, and Productive Life - Albert De Vries (EDIS)
Florida dairy producers have access to genetic evaluations for many dairy traits that are economically important. These traits are combined in economic selection indexes to rank bulls and cows for total profitability. The first economic selection index, introduced in 1971 by the USDA-Animal Improvement Programs Laboratory (USDA-AIPL) in Beltsville, MD, included only milk and fat yield. But other traits, such as the ability to get pregnant in time or to avoid culling, determine a cow's profitability as well. This document is AN158, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November, 2005.